(untitled) (Journal of Foreign Language Studies, 2020)
This action research aims to investigate how the use of Trello app can increase the effectiveness of students’ group work and teachers’ fair assessment as well as to provide recommendations for applying it in the future. This study was conducted during a 15-week translation course for third-year English majors. Observations and interviews were employed to collect data. The findings of the study show that Trello app may offer students a convenient and useful platform on which they can divide work, manage their peer involvement and provide comments for each other. Also, teachers can have more precise assessment of each student’s competence and group work skill thanks to this app.